A new species of the genus Papirioides (Collembola: Dicyrtomidae) from China - Li, Zhao-Hui; Chen, Jian-Xiu; Li, Jing (Zootaxa, 2007)
A new species, Papirioides zhejiangensis, is described from Zhejiang Province of East China. It shares the presence of a dorsal club on the great abdomen with the two Indonesian species, P. tonsori Greenslade 1994 and P. jacobsoni Folsom 1924, and the Japanese species P. uenoi Uchida 1957. The new species is close to P. tonsori in the circumanal and dens setae; however, it differs from the latter in the facial setal pattern, length of dorsal club on the great abdomen, and number of short spines on the club. It is very similar to P. jacobsoni in the color pattern; however, it is readily distinguished from the latter by the facial setal pattern, length of dorsal club on the great abdomen, circumanal setae and other features. A species list and a key to the species of the genus are provided.